Improving phosphorus acquisition efficiency through modification of root growth responses to phosphate starvation in legumes - Chen, Zhijian; Wang, Linjie; Cardoso Arango, Juan Andrés; Zhu, Shengnan; Liu, Guodao; Rao, Idupulapati M.; Lin, Yan (Frontiers Media, 2023)
Phosphorus (P) is one of the essential macronutrients for plant growth and development, and it is an integral part of the major organic components, including nucleic acids, proteins and phospholipids. Although total P is abundant in most soils, a large amount of P is not easily absorbed by plants. Inorganic phosphate (Pi) is the plant-available P, which is generally immobile and of low availability in soils. Hence, Pi starvation is a major constraint limiting plant growth and productivity. Enhancing plant P efficiency can be achieved by improving P acquisition efficiency (PAE) through modification of morpho-physiological and biochemical alteration in root traits that enable greater acquisition of external Pi from soils. Major advances have been made to dissect the mechanisms underlying plant adaptation to P deficiency, especially for legumes, which are considered important dietary sources for humans and livestock. This review aims to describe how legume root growth responds to Pi starvation, such as changes in the growth of primary root, lateral roots, root hairs and cluster roots. In particular, it summarizes the various strategies of legumes to confront P deficiency by regulating root traits that contribute towards improving PAE. Within these complex responses, a large number of Pi starvation-induced (PSI) genes and regulators involved in the developmental and biochemical alteration of root traits are highlighted. The involvement of key functional genes and regulators in remodeling root traits provides new opportunities for developing legume varieties with maximum PAE needed for regenerative agriculture.